Microstructural evolution during solution treatment of Co-Cr-Mo-C biocompatible alloys - Giacchi, Jessica Vanina (2012)
Three different Co-Cr-Mo-C alloys conforming to ASTM F75 standard were poured inan industrial environment and subjected to a conventional solution treatment at1225 °C for several time intervals. The microstructural changes andtransformations were studied in each case in order to evaluate the way in whichtreatment time influences the secondary phase fraction and clarify themicrostructural changes that could occur. To assess how treatment time affectsmicrostructure, optical microscopy and image analyzer software, scanningelectron microscopy and energy dispersion spectrometry analysis were employed.The main phases detected in the as-cast state were: σ-phase, M6C, and M23C6carbides. The latter presented two different morphologies, blocky type andlamellar type. Despite being considered the most detrimental feature tomechanical properties, σ-phase and lamellar carbides dissolution took place inthe early stages of solution treatment. M23C6 carbides featured two differentbehaviors. In the alloy obtained by melting an appropriate quantity of alloyedcommercial materials, a decrease in size, spheroidization and transformationinto M6C carbides were simultaneously observed. In the commercial ASTM F75alloy, in turn, despite being the same phase, only a marked decrease inprecipitates size was noticed. These different behaviors could be ascribed tothe initial presence of other phases in the alloy obtained from alloyedmaterials, such as σ-phase and pearlitic carbides, or to the initialprecipitate size which was much larger in the first than in the commercial ASTMF75 alloy studied. M6C carbides dissolved directly in the matrix as they couldnot be detected in samples solution-treated for 15 min.